Measuring KS0K± interactions using pp collisions at √s=7 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Köhler, Markus Konrad; Leardini, Lucia; et al. (Physics letters, 2019)
We present the first measurements of femtoscopic correlations between the KS0 and K± particles in pp collisions at s=7 TeV measured by the ALICE experiment. The observed femtoscopic correlations are consistent with final-state interactions proceeding solely via the a0(980) resonance. The extracted kaon source radius and correlation strength parameters for KS0K− are found to be equal within the experimental uncertainties to those for KS0K+. Results of the present study are compared with those from identical-kaon femtoscopic studies also performed with pp collisions at s=7 TeV by ALICE and with a KS0K± measurement in Pb-Pb collisions at sNN=2.76 TeV. Combined with the Pb-Pb results, our pp analysis is found to be compatible with the interpretation of the a0(980) having a tetraquark structure instead of that of a diquark.